(untitled) (Italian Journal of Public Health, 2006)
Utilisation of medicines exerts important effects on public health and health systems in different ways, including their pharmacological properties, their economic impact on health systems and their impact on the environment. Medicines cause intended therapeutic effects. Medicines are able to treat diseases, slow their progression or prevent their appearance as well as relieve symptoms. This is the reason why physicians prescribe, patients use and governments pay for medicines. Some therapeutic classes of drugs represent important progress in medicine and have dramatically improved the therapeutic approach to several diseases.As an example antiulcer agents have changed a severe disease (with fatal complications), requiring gastric surgical resection, into a disease requiring only the consumption of few pills each day for a short period of time, with a substantial improvement in prognosis and quality of life for patients. Avoiding the surgical intervention of gastric resection, and all of its complications, has resulted in substantial gains for individual patients and public health as well as a substantial reduction in the costs of hospitalisation. For other therapeutic classes the benefits are more limited, while the advantages of their use in everyday practice are less evident.